Knowledge management strategy in Malaysia - A. Rahman, Badruddin (2004)
A study on Knowledge Management (KM) initiatives was conducted on a sample of various categories of organization in Malaysia.The categories were companies listed in the Kuala Lumpur Stock Exchange (300 of a total of 500 companies), government Ministries and Departments (30), educational institutions (80), small and medium size industries (100), the electronic industries (150) and government-owned agencies (10).About 303 questionnaires were returned and the preliminary findings showed nearly half of the respondents were reporting that they already established formal knowledge management initiatives in their respective organizations.This was evident amongst organizations in the education sector, government own organizations and government departments and/or agencies.Nonetheless, the findings also showed that the Malaysian private sector was slowly catching up to meet the challenges of the competitive business environment.